1979
DOI: 10.1159/000122866
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Feminine Sexual Behavior in Castrated Male Rats by Intrahypothalamic Implants of Estradiol Benzoate

Abstract: The effects of intracerebral estradiol benzoate (EB) implants upon lordosis behavior in castrated male rats were investigated. 27 gauge EB-filled or Blank implants were placed unilaterally in either the preoptic area (POA) or the region of the ventromedial hypothalamic nucleus (VMH). When 0.5 μg of EB was administered subcutaneously for eight days, males with EB implants had significantly higher lordosis quotients (LQ) than males with Blank implants. EB implants located in the region of the VMH were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…While other studies have demonstrated local effects of steroid induced expression of vasopressin mRNA in the BST (Brot et al, 1992), the present study demonstrates an elevation of CCK mRNA in the projection site of the BST. It is well known that there are sites in the brain where direct application of estrogen stimulates lordosis behavior (e.g., the VMH) (Davis and Barfield, 1979;Davis et al, L982;Lisk, 1962). The present results suggest that besides local effects, estrogen implants may regulate the expression of molecules through a transsynaptic mechanism in projection sites that affect behavior.…”
Section: Site-specific Implantationsupporting
confidence: 54%
“…While other studies have demonstrated local effects of steroid induced expression of vasopressin mRNA in the BST (Brot et al, 1992), the present study demonstrates an elevation of CCK mRNA in the projection site of the BST. It is well known that there are sites in the brain where direct application of estrogen stimulates lordosis behavior (e.g., the VMH) (Davis and Barfield, 1979;Davis et al, L982;Lisk, 1962). The present results suggest that besides local effects, estrogen implants may regulate the expression of molecules through a transsynaptic mechanism in projection sites that affect behavior.…”
Section: Site-specific Implantationsupporting
confidence: 54%
“…In contrast, stimulation of the POA increases copulation in male mice (44), and the expression of c-Fos in the POA is increased in male mice (43,45,46). Within the POA, implants of estradiol promote sexual behaviors in male mice (22,47,48). In female mice, lesions of the POA decrease proceptivity and increase receptivity in female mice, whereas electrical stimulation of the MPA led to persistent decreases in lordosis (49,50) without interfering with proceptivity (50).…”
Section: Discussionmentioning
confidence: 99%
“…The preoptic region was soon established as a prime site for estrogenic hormone action in the brain (20); for instance, the preoptic region is the most effective brain site for estradiol application to enhance running wheel activity (20,21). With regard to sexual behaviors, application of estradiol to the preoptic region enhances copulatory behaviors (22), and preoptic implants of estrogen facilitate maternal care in female rats (23). Within the preoptic region, the most abundant receptor for estrogen is ERα, and binding of estradiol to ERα is necessary for facilitation of locomotion and maternal behaviors; in fact, animals with ERα knocked out exhibit significant impairments in maternal care and often display infanticidal behaviors (24).…”
mentioning
confidence: 99%
“…The role of the VMH in feminine sexual behavior is established due to its expression of steroid receptors (23,42), the behavioral responses to the locally administered estrogens (43), the impaired sexual behavior by VMH lesions (44,45), the facilitated lordosis reflex by electrical stimulation in the VMH (46), and the efferent connections of the VMH underlying female reproductive behaviors (47). Within the VMH, SF-1 plays an essential developmental role in establishing and maintaining morphological integrity for a functional nucleus.…”
Section: Discussionmentioning
confidence: 99%